6(7a-10)=

Simple and best practice solution for 6(7a-10)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(7a-10)= equation:


Simplifying
6(7a + -10) = 0

Reorder the terms:
6(-10 + 7a) = 0
(-10 * 6 + 7a * 6) = 0
(-60 + 42a) = 0

Solving
-60 + 42a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '60' to each side of the equation.
-60 + 60 + 42a = 0 + 60

Combine like terms: -60 + 60 = 0
0 + 42a = 0 + 60
42a = 0 + 60

Combine like terms: 0 + 60 = 60
42a = 60

Divide each side by '42'.
a = 1.428571429

Simplifying
a = 1.428571429

See similar equations:

| -6(2x+7)=-20+5x | | 2x+39=9x-86 | | -21=9+3(b-6) | | 1/4^4-1/7x^2-36=0 | | -34+2r=8(7r-6) | | 9x+20=5x-8 | | ((3-5x)/3)-((1-8x)/4)=((4(3-5x)-3(1-8x))/12) | | 30=3x+y | | 2cos^2x+sin(3x)=2 | | 14+12=10+2x | | p=25ln(5000-x) | | x(2+y)=6x | | (x+2)*ln(x+2)-x-2=0 | | -32=-7a-12+3a | | -32=7a-12+3a | | 629+(638+738)=7389 | | 3x/6-2/6 | | 206+-1.8b=1033 | | 5a+9b=1033 | | -(x+7)=8x-23 | | .6(x+2)=.55(2x+3) | | 4b+31.5=256 | | 4(a+1)-5=6a+5 | | ?/2000*100=2.5 | | f(f(x))+4f(x)=6-x^4 | | tanx/2=-1 | | 2.5=e-4 | | -x-3=-10x-13 | | ((8.92*10^-7)/x^(19/7))^4 | | ((8.92*10^-7)/x^(19/))^4 | | log(8/16) | | (459.3x^2)*(0.61x^(5/7)) |

Equations solver categories